2013
DOI: 10.1073/pnas.1303346110
|View full text |Cite
|
Sign up to set email alerts
|

Energetic cost of brain functional connectivity

Abstract: The brain's functional connectivity is complex, has high energetic cost, and requires efficient use of glucose, the brain's main energy source. It has been proposed that regions with a high degree of functional connectivity are energy efficient and can minimize consumption of glucose. However, the relationship between functional connectivity and energy consumption in the brain is poorly understood. To address this neglect, here we propose a simple model for the energy demands of brain functional connectivity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
421
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 473 publications
(478 citation statements)
references
References 46 publications
34
421
3
2
Order By: Relevance
“…34 Similarly, another magnetic resonance spectroscopy and rsfMRI study showed correlations between glutamate in a posterior medial cortex ROI and connectivity within the DMN. Perhaps most convincingly, Tomasi et al 19 found positive correlations between global degree (a measure of overall connectivity) and rMRGlu in regions largely overlapping the posterior DMN in a large study of 54 healthy individuals. The most important point separating our study from these results is that prior studies examined the relationship between metabolism and connectivity across subjects, generally in focal areas, while we examined the same parameter within subjects across all gray matter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Similarly, another magnetic resonance spectroscopy and rsfMRI study showed correlations between glutamate in a posterior medial cortex ROI and connectivity within the DMN. Perhaps most convincingly, Tomasi et al 19 found positive correlations between global degree (a measure of overall connectivity) and rMRGlu in regions largely overlapping the posterior DMN in a large study of 54 healthy individuals. The most important point separating our study from these results is that prior studies examined the relationship between metabolism and connectivity across subjects, generally in focal areas, while we examined the same parameter within subjects across all gray matter.…”
Section: Discussionmentioning
confidence: 99%
“…18 The DMN was originally identified as the network of regions that are most metabolically active at baseline. New research in healthy controls indicates that connectivity, or the magnitude of fluctuations of the functional magnetic resonance imaging (fMRI) signal, is related to glutamate use across healthy subjects in both the DMN and dorsal attention network, 19 and that these functional networks also display the greatest degree of aerobic glycolysis. 20 It is unknown whether these relationships are preserved in subjects with TLE.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the tight coupling between synaptic strength, glutamate cycling, and neuroenergetics (Abdallah et al, 2014;Hyder et al, 2013), it is important to highlight that GBCr has been found to positively correlate with rCBF (Liang et al, 2013). Similarly, other GBC-type measures were positively associated with rCBF and cerebral metabolic rate of glucose (Liang et al, 2014;Tomasi et al, 2013). In this context, the observed PFC reduction in GBCr could be an indirect measure of chronic stress-induced synaptic dysconnectivity.…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, we performed two sensitivity analyses in which (a) we examined the potential impact of malnutrition on our resting-state connectivity findings by assessing group differences in the ALFF in blood-oxygen-level dependent (BOLD) signal, a proxy measure of glucose metabolism in the brain (Nugent et al, 2015;Tomasi et al, 2013), within the thalamus, AntPFC, and DLPFC and (b) we assessed the extent to which current BMI, one index of malnutrition, correlated with our main study findings in the AN group. We found no group differences in ALFF within any of the examined thalamofrontal regions, suggesting that the AN group did not exhibit alterations in BOLD signal that may have confounded the results of our resting-state connectivity analyses.…”
Section: Discussionmentioning
confidence: 99%